Konsep Deradikalisme dan Kontra Terorisme menurut Said Nursi - Faiz, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Positive action (al-'amal al-ijabi) is a basic rule which became the principle thought of Said Nursi (1877-1960) in creating a sense of security and peace of mankind in general and happiness especially for Muslims in this day and hereafter. The most important positive deeds according to Nursi is affirming faith in order to achieve the pleasure of Allah s.w.t., because the greatest symbol and the culmination of all the positive activities of mankind is serving for a faith. Thus, this study will reveal Nursi’s concept in an effort to de-radicalization and counter-terrorism as an issue of humanity until now. This study uses qualitative methods in analyzing the thoughts and ideas of Said Nursi in realizing the positive action and avoiding destructive action based on a review of literature on his work “Risale-i Nur”. Some important results of this study state that the principle thought of Nursi is based on the values ​​of al-Quran and al-Hadith who brought the message of peace and always avoid the negative actions. According to Nursi, edifying the education, strengthening positive values ​​in social life by promoting love and affection and initiating the true jihad (al-jihad al-ma'nawi) are real solutions to save humanity from radicalism and terrorism.